The Implementation and First‐Round Results of a Community‐Based Colorectal Cancer Screening Program in Shanghai, China. (14th March 2018) - Gong, Yangming; Peng, Peng; Bao, Pingping; Zhong, Weijian; Shi, Yan; Gu, Kai; Zheng, Ying; Wu, Chunxiao; Cai, Sanjun; Xu, Ye; Sheng, Jun; Wu, Fan
Abstract : Background: The incidence and mortality rate of colorectal cancer (CRC) have increased dramatically over the past 3 decades in China due to changes in lifestyle factors. Early detection and treatment guidelines for asymptomatic cases have shown to improve CRC control in developed countries. In response to these challenges, the Shanghai Municipal Government launched a community‐based CRC screening program in 2012. Materials and Methods: Free initial screening, inclusive of immunochemical fecal occult blood and risk assessment (questionnaire), was provided by community health centers in Shanghai. Participants with positive results were referred to a specialist for a colonoscopy. Results: In 2013, 828, 302 Shanghai residents were registered; 97.7% (809, 528) of the registrants completed initial screening. Among 180, 094 initial screening‐positive participants, 71, 733 underwent colonoscopy. The proportion of compliance to colonoscopy was 39.8%; the proportion decreased with age and educational level. A total of 6, 668 adenomas were detected, and 1, 630 CRC cases were diagnosed. The CRC detection rate of the program was 201.35/100, 000; among the detected CRCs, 51.6% were in stage 0–I. Conclusion: The screening program achieved great progress, especially on initial screening completion and CRC early stage rate, although particular intervention is still needed to improve the compliance of colonoscopy. Implications for Practice: Due to socioeconomic transitions and lifestyle changes, colorectal cancer is now becoming one of the most common cancers in developing countries, as it is in developed countries. While most developed countries have now initiated national colorectal cancer screening programs based on recommended country‐specific colorectal cancer screening guidelines, colonoscopy has become the most commonly used screening method. This is a challenge in developing countries due to limited resources. Based on the analysis of the Shanghai colorectal cancer screening program, with immunological fecal occult blood test and risk assessment as initial screening, followed by a diagnostic testing of colonoscopy for individuals with positive results, this article provides the basis and suggestion for similar program in other regions of China and other developing countries. Abstract : There is good evidence of the benefits of early detection of cancer and removal of adenomas in asymptomatic individuals; however, the widespread implementation of colorectal screening programs is resource‐dependent. Such programs have been widely implemented in high‐income regions and countries in North America, Europe, Japan, and South Korea, but such programs are few in low and middle‐income countries [35]. This article describes the implementation of a comprehensive approach to colorectal cancer screening in Shanghai, China.